Evaluation of Voltage Profile in ETAP (Electric Transient And Analysis Program) at Ahuru Feeder 20 kV Medium Voltage Distriution - A. F. Haurissa, Marceau; Jamlaay, Marselin; Parera, Lory M. (International Journal of Science, Technology & Management, 2024)
Ahuru feeder is the feeder with the longest network of all Ambon city distribution networks. So it is predicted that losses will occur in the network because the longer the distribution channel, the greater the voltage drop. Voltage drops in the network cause energy losses (losses) which need to be evaluated and anticipated whether they occur within normal and reasonable limits. So in this research an evaluation of the voltage profile of the Ahuru feeder was carried out using the power flow analysis method using ETAP 12.6.0 software. Based on the simulation results, under installed load conditions, there is a voltage drop below the PLN standard on the BusL-ERIE3 line of 18.99kV or 95% up to the end of the BusL-WAYOMAR series network of 18.907kV or 94.5% of the nominal voltage of 20 kV. Meanwhile, the base, middle and end line voltage profiles are based on simulation results, the installed load conditions produce a base voltage level of 19.77kV with a voltage drop of 1.2%, the middle of the line 19.09kV with a voltage drop of 3.3% and the end of the line 18.907kV with a voltage fell by 4.3%. Repairing the line voltage profile using capacitor banks on lines and buses that experience voltage drops, namely on BusL-ERIE3 of 2x400 kVAR, is able to improve the voltage profile at the base of the line by 19.804kV or 99%, the middle of the line 19.24kV or 96.2% and the end 19,074kV line or 95.4%.